EFFECTIVENESS OF CARDIAC SCREENING INCLUSIVE OF ECG IN YOUNG ATHLETES. Issue 7 (11th March 2014) - Toresdahl, B; Pelto, H; Fudge, J; Harmon, K; Rao, A; Asif, I; Owens, D; Prutkin, J; Salerno, J; Drezner, J
Abstract : Background: The primary objective of pre-participation screening in athletes is the detection of potentially lethal cardiac conditions. The American Heart Association (AHA) recommends a directed history and physical examination. The added value of electrocardiogram (ECG) screening is debated  . Objective: To determine the effectiveness of different cardiac screening strategies in young competitive athletes. Setting: Heart screening events in U.S. high schools from October 2010 through June 2013. Patients: Competitive athletes ages 13-19. Interventions: Heart health questionnaire and physical examination based on AHA recommendations, resting 12-lead ECG, and echocardiogram if indicated. Main outcome measurements: Prevalence of potentially lethal cardiac conditions, false-positive results, and positive predictive value for testing procedures. Results: 4, 812 athletes underwent cardiac screening (54% male, 46% female; 65% Caucasian, 10% Asian, 6% African-American, and 19% other). 23 athletes (0.5%, 1 in 209) were identified with a potentially lethal cardiac condition including 9 Wolff-Parkinson-White, 4 coronary artery anomaly, 3 dilated aortic root/aneurysm, 3 long QT syndrome, 2 hypertrophic cardiomyopathy, 1 ventricular arrhythmia, and 1 short QT syndrome. Abnormal history or physical findings led to the diagnosis in 14/23 (61%) disorders and an abnormal ECG led to the diagnosis in 16/23 (70%). The addition of ECG led to detection of 7/23 (30%) athletes not otherwise identified by the AHA protocol. One case was identified by echocardiography without a relevant abnormality on history, physical, or ECG. Conclusions: Standardized history and physical examination has a high false-positive rate in cardiac screening of young athletes. ECG screening using modern interpretation criteria provides a low false-positive rate and increases the likelihood of detecting disorders associated with sudden cardiac death. An integrated screening protocol using history, physical examination, and ECG is recommended for pre-participation screening in young athletes.